Cayetano Heredia: A departure and a prolonged illness - Zárate-Cárdenas, Eduardo (2013)
Much praise has been given to Cayetano Heredia's role as first dean of the Medical College of Lima. Less common are mentions on interruptions this work suffered as a result of the Peru's first decades’ economic turmoil and Heredia's own ailing health. This text draws on primary sources to share a new look on Heredia's remarkable achievements, the reasons behind his departure from his role -despite ample recognition of his work in Peruvian medical society- and the chronic illness that would lead to his ultimate death.